KONFLIK MINORITAS MELAYU DAN MILITER THAILAND ANALISIS TERHADAP KRISIS POLITIK DI SELATAN THAILAND - Yasril Yazid (Lembaga penelitian dan pengabdian kepada masyrakat, 2009)
Political crisis in southern Thailand today can be regarded as manifestation of conflict between two of nature, namely the traditional context of the Sultanate of Pattani which is part of nature Malay (Malay world) and the status of these territories as part of the modern kingdom of Thailand oriented Buddhist world-view. Dualism between traditional (historical nature) with the contemporary as today's reality, is one of the main causes of conflict in these areas